Diarrhea Prediction Model of Children Under Five Based on Sanitation Means - Erlani, Erlani; Sulasmi, Sulasmi; Akbar, Fajar; Mulyadi, Mulyadi; Haderiah, Haderiah; Mappau, Zrimurti (Jurnal Kesehatan Manarang, 2024)
The Lamuru Health Center area has the highest number of diarrhea sufferers and is included in the top 10 most common diseases. The sanitation conditions of the house still need to be improved, as well as health requirements, such as clean water facilities, wastewater, family toilets, and waste management. The study aims to determine the prediction model of diarrhea in children under 5 years of age based on sanitation facilities in the village of Massenreng Pulu, Lamuru district, Bone Regency. This type of research is analytical and observational. The population in the study were all housewives who had toddlers in Massenreng Pulu Village, Lamuru District, Bone Regency, totaling 120 people. The study sample was mothers with toddlers as respondents, totaling 120 people, using the selection method selected by total sampling—data analysis with logistic regression test. The results show that there are three insignificant variables: clean water facilities (p-value= 0.500 (OR=0,652), toilet facilities p-value=0.808 (OR=0,895), and waste disposal facilities p-value= 0.922 (OR=0,928), meaning that the three variables do not affect the incidence of diarrhea toddlers. While the variable wastewater disposal facilities are significant, with a p-value=0.004 (OR=3,320), there is an influence on the incidence of diarrhea. This study concludes that clean water, toilets, and waste disposal facilities do not affect the incidence of diarrhea, so they cannot be included in the prediction model. Meanwhile, the variable sewerage facilities can enter predictive models with the incidence of diarrhea. There is a possibility of diarrhea occurring if the recommended wastewater conditions do not meet the requirements. It should make wastewater drainage channels that meet the requirements through government programs and with the help of local communities so that the sewerage is made permanently, waterproof, closed, and not humid.